Caracterização estrutural dos compostos Ca2MnReO6 e Ca1,8Ce0,2MnReO6 através da técnica de absorção de raio X - Rodrigues, Erika Laurina Oliveira (2014)
In this work will be presented a description about the synthesis methodsusing solid state reaction using the encapsulated quartz tube technique and a description about the morphogolical and strutural characteristics of the compounds Ca2MnReO6and Ca1,8Ce0,2MnReO6. The analysis of the diffraction patternusing Rietveld show us that the dopped sample doped with 5% cerium is monophasic to and it was also possible to note an expansion of the unit cell without changing the symmetry of the doped sample. The electron microscopy images showed a homogeneous size and shape of the particles in the sample. The measurements of X-ray absorption by synchrotron radiation at the edge K of Mnand the edge L3of Reshow that both elements have mixed valence in samples with and without doping , assuming a value for Re+7 in the doped , while the change was not observed value the valence of Mn.